Pengaruh Penambahan Variasi Ketebalan Kain Pelapis Knalpot ( Exhaust Wrap) Terhadap Perpindahan Panas Pada Mesin Sepeda Motor 150cc - Zeva Bayu Pradana; Khambali Khambali (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
In motor vehicles, there is heat energy wasted from combustion in the combustion chamber. The temperature in a motorcycle engine has work, if it exceeds the ideal working temperature and is forced, it will be fatal. Because it will damage the cylinder wall components, pistons, and piston handlebars. The purpose of this study is to determine the effect of adding variations in exhaust wrap thickness on heat from exhaust headers and heat transfer rates. The research approach used is Quantitative, Experimental. The data collection method uses thermocouple test equipment and datalogger. The data obtained was processed into graph data and analyzed using the anova one-way method. The results showed that by adding a variety of coating cloth (exhaust wrap) to the exhaust header can reduce the temperature that comes out of the exhaust header where by coating 3 layers of exhaust wrap can reduce the most optimal heat and also reduce the heat transfer rate from testing for 1 minute, 2 minutes and 3 minutes with exhaust wrap of 17.99 J/s without exhaust wrap, 6.47 J/s 1 layer exhaust wrap and -28.10 J/s 3 layers exhuast wrap.